Approaches to analysis of higher mental function impairments - M. V. Karyakina; O. V. Rychkova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The purpose of the review is to compare the methodological approaches of Russian psychological school and Western psychology to the study of higher mental functions, and to compare the methods used for evaluating them.The comparison of methods used in Western and Russian psychodiagnostics demonstrates, that differences begin at the stage of interpreting the results. Thus, the neuropsychological analysis identifies not the loss of the mental function in general, but the impairment of it’s parts. This makes neuropsychological analysis more of a qualitative method based on the analysis of individual clinical cases.In Western psychology it is more common to talk about mental functions in general. The use of standardized tests makes it possible to use mathematical tools for data processing, makes the results comparable in different groups of subjects, and allows to extend the conclusions to the general population in accordance with modern requirements for the reliability of scientific results.